Mestrados na área de Educação Física no estado do Rio Grande do Sul: um estudo sobre o perfil dos egressos - Quadros, Helder Madruga de (2012)
The pos graduation in Brazil in its strict sense, in the last decades, has being constituted as a formation in great process of expansion and in the scientific community knowledge consolidation, as in Masters and as PDH s degrees. In this context, the present study has as main goal to describe the Masters Degree students profile in the Physical Education strict-census pos graduation program, in the Physical Education higher education in Federal University of Pelotas (ESEF/UFPel) and the Human Movement science in the Physical Education higher education in Federal University of Rio Grande do Sul (ESEF/UFRGS). This profile description had as essential focus the academic formation and the Masters Degree student s current profession in the period of before, during and after their Masters conclusion. These two programs were chosen for being the only two in Physical Education s area in operation in the state of Rio Grande do Sul (RS) in the specific period of this research. The study is a descriptive work, wish documental basis, characterized by a qualitative approach achieved through the data analysis referred to the Lattes Curriculum of the Masters Degree students. There were collected and analyzed data from 117 curriculums, 81 from ESEF/UFRGS and 36 from ESEF/UFPel, from Masters Degree students enrolled from 2008 to 2010. The main results have revealed that most of the students are from the female gender, with 52,14%, 32,48% of the students had obtained scholarships, 97,56% of the higher graduation course concluded by the students are in the health area, 95,94% of the graduation courses happen in the state of RS, mostly in private institutions, more than 3/4 of the students have already done a pos graduation in the level of a specialization, 29,91% had entered the Doctors and 62,39% are working as professors and teachers in higher and in primary education. Based on the researched literature and taking in consideration that the preparation for being a professor is one of the main goals in pos graduation courses, the results indicate that both programs are fulfilling with its role in Brazilian s pos graduation development. Is up to bring the attention that the data reveled similarities and differences between ESEF/UFRGS and ESEF/UFPel programs and that more researches about the Masters Degree students, in the Physical Education area, enabling a deepen in the discussions that permeate the construction and the consolidation of these programs